On the boundary behavior of solutions of the Beltrami equations - Kovtonyuk, D. A.; Petkov, I. V.; Ryazanov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We show that every homeomorphic solution of the Beltrami equation f = μ f in the Sobolev class W^1, 1_loc is a so-called lower Q-homeomorphism with Q(z) = K_μ(z), where K_μ is a dilatation quotient of this equation. On this basis, we develop the theory of the boundary behavior and the removability of singularities of these solutions.